The Relationship Between Fasting Blood Glucose Levels and Lipid Profiles in Type 2 Diabetes Mellitus Patients at the Abdalas Padang Community Health Center - Telambanua, Arniat Christiani (Rajaki of Tulip Medika Publisher, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disease characterized by impaired glucose and lipid metabolism, increasing the risk of dyslipidemia, which contributes to cardiovascular complications. This study aims to determine the relationship between fasting blood glucose (FBG) levels and lipid profiles in T2DM patients at Andalas Padang Community Health Center. This study used an analytical design with a cross-sectional approach based on medical record data. The study sample consisted of 88 randomly selected T2DM patients. Data were analyzed using the Spearman correlation test. The results showed that the majority of patients had high FBG levels (83.0%), normal total cholesterol (77.3%), low HDL (81.8%), high triglycerides (71.6%), and high LDL (38.6%). Bivariate analysis showed a significant relationship between FBG and triglycerides (p = 0.036) and LDL (p = 0.055). Meanwhile, there was no significant relationship between FBG and total cholesterol (p = 0.097) or HDL (p = 0.102). This study concludes that there is a relationship between GDP levels and triglycerides and LDL in type 2 DM patients. Suggestions, health workers are expected to increase monitoring of lipid profiles, especially LDL, in type 2 DM patients. Patients are also advised to comply with diet, physical activity, and drug therapy.